Comparative study of efficacy and adverse effects of different doses of vaginal misoprostol for cervical ripening 10-12 hours before diagnostic hysteroscopy - Gupta, Taru; Ahmad, Syed Nawaz; Kumari, Sonu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysteroscopy first described by Panteleoni in 1869 has evolved into a standard procedure for the diagnosis and treatment of intrauterine pathologies such as polyps, fibroids, septae, adhesions, evaluation of abnormal uterine bleeding, evaluation and treatment of infertility, removal of an intrauterine device or foreign body. Present study was carried out to compare the efficacy and complications different doses of vaginal misoprostol for cervical ripening10-12 hours before diagnostic hysteroscopy. Methods: It was a prospective and interventional, double-blinded randomized comparative study. Sixty women, fulfilling the inclusion criteria, requiring diagnostic hysteroscopy for evaluation of infertility were enrolled. The study subjects randomly received either 200μg (group 1) or 400μg (group 2) of vaginal misoprostol 10-12 hours before hysteroscopy with equal number of subjects in both the groups. Hysteroscopy was performed with a standard rigid 6 mm and 300 hysteroscope. The largest dilator that could be inserted without resistance was recorded as the baseline cervical dilatation. The ease of dilatation was recorded on a 5 point LIKERT scale. Procedural time was measured as time taken from the beginning of cervical dilatation to the visualisation of the uterine cavity. Results: The mean base line cervical width in group 1 was 6.41±0.29 mm while in group 2 it was 6.43±0.21 mm (p=0.084). In group 1, 26.6% patients had very easy entry, 53.4% had easy entry while in group 2, 30% patients had very easy entry, 43.4% had easy entry. The mean procedural time 35.5±6.9 seconds in group 1 and 33.2±6.8 seconds in group 2 (p=0.212). Adverse effects like abdominal pain, vaginal bleeding, shivering and fever were observed more often in group 2 compared to group 1(p=0.038). Conclusions: Two hundred microgram of vaginal misoprostol is safer and equally effective as 400 μg for cervical ripening when used 10-12 hours before diagnostic hysteroscopy.